Upper urinary dilatation and treatment of 26 patients with diabetes insipidus: A single-center retrospective study - Wang, Xuesheng; Ying, Xiaoqian; Zhang, Fan; Li, Xing; Chen, Guoqing; Zhou, Zhonghan; Liao, Limin (Frontiers in Endocrinology, 2022)
Objective: To describe the urinary tract characteristics of diabetes insipidus (DI) patients with upper urinary tract dilatation (UUTD) using the video-urodynamic recordings (VUDS), UUTD and all urinary tract dysfunction (AUTD) systems, and to summarize the experience in the treatment of DI with UUTD. Methods: This retrospective study analyzed clinical data from 26 patients with DI, including micturition diary, water deprivation tests, imaging data and management. The UUTD and AUTD systems were used to evaluate the urinary tract characteristics. All patients were required to undergo VUDS, neurophysiologic tests to confirm the presence of neurogenic bladder (NB). Results: VUDS showed that the mean values for bladder capacity and bladder compliance were 575.0 ± 135.1 ml and 51.5 ± 33.6 cmH2O in DI patients, and 42.3% (11/26) had a post-void residual >100 ml. NB was present in 6 (23.1%) of 26 DI patients with UUTD, and enterocystoplasty was recommended for two patients with poor bladder capacity, compliance and renal impairment. For the 24 remaining patients, medication combined with individualized and appropriate bladder management, including intermittent catheterization, indwelling catheter and regular voiding, achieved satisfactory results. High serum creatinine decreased from 248.0 ± 115.8 μmoI/L to 177.4 ± 92.8 μmoI/L in 12 patients from a population with a median of 108.1 μmoI/L (IQR: 79.9-206.5 μmoI/L). Forty-four dilated ureters showed significant improvement in the UUTD grade, and the median grade of 52 UUTD ureters decreased from 3 to 2. Conclusion: Bladder distension, trabeculation and decreased or absent sensations were common features for DI patients with UUTD. Individualized therapy by medication combined with appropriate bladder management can improve UUTD and renal function in DI patients.